Adsorption of per- and polyfluoroalkyl substances (PFAS) by quaternary ammonium and fluorine-functionalized macrocyclic sorbents: A comprehensive experimental and simulation study - Yilang Sun; Ameevardhan Singh Patyal; George Hana; Ke Wu; Isreq Real; Chao Zhou; Jennifer L. Guelfo; Joshua D. Howe; Yuexiao Shen (Water Research, 2026)

Long-Term Treatment with Alcaligenes faecalis A12C Improves Host Resistance to Pathogens in Septic Rats: Possible Contribution of Curdlan-Like Immune Trainer - C. J. Martel-Benítez; R. Alayón-Afonso; D. Padilla Castillo; F. J. Chamizo-López; M. Isabel García-Laorden; A. Espinosa de los Monteros y Zayas; J. C. Rivero-Vera; P. Nogueira Salgueiro; F. Real; A. Bordes-Benítez; A. Martel Quintana; C. Almeida Peña; et al. (Probiotics and Antimicrobial Proteins, 2025)
Curdlan, a β-1,3/1,6-glucan found in Alcaligenes faecalis ( A. faecalis ) wall, activates innate and humoral immunity. The aim of this study is to evaluate whether pretreated rats with A. faecalis A12C could prevent sepsis disturbances and identify the immunomodulatory mechanisms involved. Experiments occurred in two stages: a survival study with 16 rats randomly divided into septic (SC) ( n = 8) and septic pretreated (SA) ( n = 8) groups and 45 rats divided into four groups: healthy (AGUSAN) ( n = 9), septic (AGUIC) ( n = 13), septic pretreated (AGUIA) ( n = 14), and healthy pretreated (AGUSTO) ( n = 9). Sepsis was induced by cecal ligation and puncture after 30 days of A. faecalis A12C pretreatment or without. SA group had a higher survival rate of 58% vs. 16% for SC group ( P < 0.05). Overall, AGUIA showed better status than AGUIC ( P < 0.01). Higher monocytosis was found in AGUIA and AGUSTO vs. AGUIC and AGUSAN, respectively ( P < 0.05). A gradual increase in curdlan fecal concentration was observed in AGUIA during pretreatment. Fecal concentrations of Escherichia coli significantly decreased in AGUIA and AGUSTO. Bacterial load in urine, peritoneal lavage fluid (PLF), and bronchoalveolar lavage fluid (BALF) decreased ( P < 0.05) in AGUIA vs. AGUIC. Finally, lower inflammation was observed in serum, BALF, and PLF, with reduced IL-6, IL-10, IL-1β, and TNF-α, along with less damage in lungs and peritoneum in AGUIA vs. AGUIC. These findings suggest the connection between curdlan—produced by A. faecalis A12C—with the immune system and the reduction in severity of experimental sepsis.

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Neuroimaging and immunofluorescence of the Pseudopus apodus brain: unraveling its structural complexity - S. Jiménez; R. Morona; M. J. Ruiz-Fernández; E. Fernández-Valle; D. Castejón; M. I. García-Real; J. González-Soriano; N. Moreno (Brain Structure and Function, 2025)
The present study provides an in-depth neuroanatomical characterization of the brain of Pseudopus apodus , combining magnetic resonance imaging (MRI) with histological analysis by immunofluorescence. In the telencephalon, the pallial regions showed distinct anatomical features, including a cortical structure, a dorsal ventricular ridge and the spherical nucleus, but prominent layering patterns, observable on histological slides, were not fully resolved by MRI. Subpallial structures, such as the nucleus accumbens and the basal ganglia, were delineated with histological clarity and further supported by MRI. In the hypothalamic and diencephalic regions, the dense and complex cellular composition made precise delineation of individual nuclei difficult by MRI, in contrast to the histological accuracy, however by MRI the identification of the major tracts running through these domains are clearly identifiable. Mesencephalic and rhombencephalic structures, including the optic tectum, isthmic nuclei, cerebellum, and reticular groups, were systematically described using a combination of histological and MRI techniques. In addition, immunofluorescence analysis of specific markers, such as Calretinin, ChAT, Isl1, Satb1, Serotonin and Tyrosine Hydroxylase, provided higher resolution of functional sub-regions, allowing precise identification of boundaries and facilitating comprehensive regional mapping, showing complex organizational arrangements, both in rostral regions, such as the dorsal ventricular crest, and in caudal regions, within the tegmental and posterior nuclei of the brain, including the ventral tegmental area, substantia nigra and raphe nuclei. These findings establish a robust neuroanatomical framework for Pseudopus apodus , contributing significantly to the understanding of reptile brain organization and providing valuable insights into the evolutionary adaptations underlying a limbless lizard neuroanatomy.

Determination of Mixing Efficiency in Various Laboratory-Scale Semi-Solid Formulation Techniques Through Computational Fluid Dynamics and Finite Volume Simulations - Emiliano Frenquelli; Juan P. Real; Juan M. Llabot; Liliana Pierella; Santiago D. Palma; Daniel A. Real (Journal of Pharmaceutical Innovation, 2025)

Assessment of the Influence of Various Degrees of Conicity in Pharmaceutical Reactors on Mixing and Homogenization Processes, Heat Transfer, and Emptying - Emiliano Frenquelli; Juan P. Real; Juan M. Llabot; Liliana Pierella; Santiago D. Palma; Daniel A. Real (Journal of Pharmaceutical Innovation, 2025)

Corrigendum to “Avian communities respond to plant and landscape composition in actively revegetated floodplains of the Colorado River delta in Mexico” [Ecological Engineering 205 (2024) 107266]. - Eduardo González-Sargas; Martha Gómez-Sapiens; Osvel Hinojosa-Huerta; Stefanny Villagomez-Palma; Alejandra Calvo-Fonseca; Joanna Grand; Timothy D. Meehan; Chris Dodge; Pamela L. Nagler; Carlos Restrepo-Giraldo; Carlos Nieblas; Angela Meléndez; et al. (Ecological Engineering, 2025)

Avian communities respond to plant and landscape composition in actively revegetated floodplains of the Colorado River delta in Mexico - Eduardo González-Sargas; Martha Gómez-Sapiens; Osvel Hinojosa-Huerta; Stefanny Villagomez-Palma; Alejandra Calvo-Fonseca; Joanna Grand; Timothy D. Meehan; Chris Dodge; Pamela L. Nagler; Carlos Restrepo-Giraldo; Carlos Nieblas; Angela Meléndez; et al. (Ecological Engineering, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Impact of genetic diversity and antibiotic-resistance of Salmonella isolated from feral cats: One Health approach - C. Marin; M. Cerdà-Cuéllar; I. Rosario; L. Lorenzo-Rebenaque; S. Vega; A. Manzanares; D. Padilla; F. Real; E. Rodríguez-Ponce; B. Acosta-Hernández (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Increased ATP Release and Higher Impact of Adenosine A2A Receptors on Corticostriatal Plasticity in a Rat Model of Presymptomatic Parkinson’s Disease - Francisco Q. Gonçalves; Filipe C. Matheus; Henrique B. Silva; Joana I. Real; Daniel Rial; Ricardo J. Rodrigues; Jean-Pierre Oses; António C. Silva; Nélio Gonçalves; Rui D. Prediger; Ângelo R. Tomé; Rodrigo A. Cunha (Molecular Neurobiology, 2023)
Extracellular ATP can be a danger signal, but its role in striatal circuits afflicted in Parkinson’s disease (PD) is unclear and was now investigated. ATP was particularly released at high stimulation intensities from purified striatal nerve terminals of mice, which were endowed with different ATP-P2 receptors (P2R), although P2R antagonists did not alter corticostriatal transmission or plasticity. Instead, ATP was extracellularly catabolized into adenosine through CD73 to activate adenosine A 2A receptors (A 2A R) modulating corticostriatal long-term potentiation (LTP) in mice. In the presymptomatic phase of a 6-hydroxydopamine rat model of PD, ATP release from striatal nerve terminals was increased and was responsible for a greater impact of CD73 and A 2A R on corticostriatal LTP. These observations identify increased ATP release and ATP-derived formation of extracellular adenosine bolstering A 2A R activation as a key pathway responsible for abnormal synaptic plasticity in circuits involved in the onset of PD motor symptoms. The translation of these findings to humans prompts extending the use of A 2A R antagonists from only co-adjuvants of motor control in Parkinsonian patients to neuroprotective drugs delaying the onset of motor symptoms.

Probiotic Properties of Alcaligenes faecalis Isolated from Argyrosomus regius in Experimental Peritonitis (Rat Model) - A. I. Gutiérrez-Falcón; A. M. Ramos-Nuez; A. Espinosa de los Monteros y Zayas; D. F. Padilla Castillo; M. Isabel García-Laorden; F. J. Chamizo-López; F. Real Valcárcel; F. Artilles Campelo; A. Bordes Benítez; P. Nogueira Salgueiro; C. Domínguez Cabrera; J. C. Rivero-Vera; et al. (Probiotics and Antimicrobial Proteins, 2021)
A strain of Alcaligenes faecalis A12C ( A. faecalis A12C) isolated from Argyrosomus regius is a probiotic in fish. Previous experiments showed that A. faecalis A12C had inhibitory effects on the growth of multidrug-resistant bacteria. We aimed to confirm whether A. faecalis A12C is safe and has adequate intestinal colonization in experimental rats, and evaluate its efficacy in an animal model of peritonitis . We used 30 male rats, randomly divided into 6 groups ( n = 5): three groups (HA7, HA15, HA30) received A. faecalis A12C in drinking water (6 × 10 8 CFU/mL) for 7 days, and three control groups received drinking water only. All groups were evaluated at 7, 15, and 30 days. Survival after A. faecalis A12C administration was 100% in all groups. Mild eosinophilia (1.5%, p < 0.01) and increased aspartate aminotransferase (86 IU/L, p < 0.05) were observed in HA7, followed by progressive normalization. No histological signs of organ injury were found. We observed significant E. coli decline in faeces, parallel to an increase in A. faecalis A12C at 7 days. E. coli had a tendency to recover initial values, while A. faecalis A12C disappeared from the intestinal microbiota at 30 days. To evaluate its efficacy against peritonitis, we studied two additional groups of animals: IA group pretreated with A. faecalis A12C before E. coli intra-abdominal inoculation, and IC group inoculated with no A. faecalis A12C. We found an increase in C-reactive protein, alanine aminotransferase, urea, and eosinophils in IC animals when compared with IA. Peritonitis was more evident in IC than in IA animals. Our findings suggest that A. faecalis A12C altered clinically relevant parameters in sepsis and was associated with a lesser spread of infection.

A Simplified Numerical Method for the Design and Analysis of FPSO Platform Brackets Subjected to Operational Conditions - Kauê L. Martins; Vinícius T. Pinto; Cristiano Fragassa; Mauro V. Real; Luiz A. O. Rocha; Liércio A. Isoldi; Elizaldo D. dos Santos (Journal of Marine Science and Engineering, 2020)
The present work develops a simplified computational methodology to predict brackets’ mechanical behavior to support mooring systems’ fairleads under maximum environmental loads. The methodology consists of estimating environmental loads in Campos’s basin (Brazil) using standards available in the literature and applying them to determine the stress distribution in the brackets’ solid domain using a code based on the Finite Element Method. The brackets studied here are composed of AH36 steel plates. Six different geometric configurations for the brackets considering thinner plates than those ordinarily employed in the existent brackets of the P-66 Petrobras oil production platform were studied. Theoretical recommendations about geometric configurations to reduce the von Mises maximum stress in brackets’ plates were determined in the light of constructal design. The results proved the importance of the geometric investigation in this problem. For instance, for the accidental limit state (ALS) the best configuration leads to a mechanical performance two times superior to that reached for the worst one, which had a maximum stress superior to the yielding limit. Moreover, the best designs for the superior and inferior brackets in the ALS have different configurations.

Temporal Dissociation of Striatum and Prefrontal Cortex Uncouples Anhedonia and Defense Behaviors Relevant to Depression in 6-OHDA-Lesioned Rats - Filipe C. Matheus; Daniel Rial; Joana I. Real; Cristina Lemos; Reinaldo N. Takahashi; Leandro J. Bertoglio; Rodrigo A. Cunha; Rui D. Prediger (Molecular Neurobiology, 2016)

A porcine circovirus-2 mutant isolated in Brazil contains low-frequency substitutions in regions of immunoprotective epitopes in the capsid protein - Rafael Locatelli Salgado; Pedro Marcus Pereira Vidigal; Natalia F. Gonzaga; Luiz F. L. de Souza; Marcelo D. Polêto; Thiago Souza Onofre; Monique R. Eller; Carlos Eduardo Real Pereira; Juliana L. R. Fietto; Gustavo C. Bressan; Roberto M. C. Guedes; Márcia R. Almeida; et al. (Archives of Virology, 2015)

NGS metabarcoding proves successful for quantitative assessment of symbiont abundance: the case of feather mites on birds - J. Diaz-Real; D. Serrano; A. Piriz; R. Jovani (Experimental and Applied Acarology, 2015)

Impact of HIV infection on sustained virological response to treatment against hepatitis C virus with pegylated interferon plus ribavirin - P. Monje-Agudo; A. Castro-Iglesias; A. Rivero-Juárez; F. Martínez-Marcos; E. Ortega-González; L. M. Real; B. Pernas; N. Merchante; P. Cid; J. Macías; M. D. Merino; A. Rivero; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Novel in vitro systems for prediction of veterinary drug residues in ovine milk and dairy products - L. González-Lobato; R. Real; D. Herrero; A. de la Fuente; J.G. Prieto; M.M. Marqués; A.I. Álvarez; G. Merino (Food Additives & Contaminants: Part A, 2014)

Prioritisation of novel pasture species for use in water-limited agriculture: a case study of Cullen in the Western Australian wheatbelt - R. G. Bennett; M. H. Ryan; T. D. Colmer; D. Real (Genetic Resources and Crop Evolution, 2011)

First report of Streptococcus iniae in red porgy ( Pagrus pagrus , L.) - F El Aamri; D Padilla; F Acosta; M J Caballero; J Roo; J Bravo; J Vivas; F Real (Journal of Fish Diseases, 2010)
This work describes the first isolation of Streptococcus iniae in red porgy, Pagrus pagrus (L.), and the first European isolation of this pathogen in gilthead seabream, Sparus aurata (L.). In both farmed fish species, infection resulted in lethargy, anorexia, abnormal swimming, exophthalmia and sudden death, with mortality rates of over 25% in red porgy and 10% in gilthead seabream. Beta‐haemolytic Gram‐positive cocci, catalase negative and oxidase negative, were isolated in pure culture from internal organs. Conventional and rapid identification systems, and 16S rRNA gene partial sequencing were used to identify the causative agent of the natural disease. LD 50 trials were carried out to show the virulence of this isolated strain in these species, with values of 1.7 × 10 4 CFU per fish in red porgy and 1.32 × 10 5 CFU per fish in gilthead seabream. The most prominent lesions were meningoencephalitis and multifocal infiltration of macrophage cells in the kidney and spleen.

Invasion and survival of Photobacterium damselae subsp. piscicida in non‐phagocytic cells of gilthead sea bream, Sparus aurata L. - F Acosta; J Vivas; D Padilla; J Vega; J Bravo; V Grasso; F Real (Journal of Fish Diseases, 2009)
Fluorescence microscopy and gentamicin protection assays were used to investigate the ability of four Photobacterium damselae subsp. pisicida (Phdp) strains to adhere to and to invade the fish epithelial cell line, SAF‐1, derived from Sparus aurata . All strains tested were detected intracellularly using both techniques, although internalization levels varied among strains. Treatment with cytochalasin D and experiments carried out at 4 °C demonstrated that a functional host cell cytoskeleton and active cell metabolism are necessary for bacterial internalization. Intracellular bacteria were detected for up to 7 days with a round morphology and were stained with DAPI, indicating that some bacterial cells may remain viable inside SAF‐1 cells. Our in vitro findings indicate that Phdp are capable of adhering, entering and surviving within the non‐phagocytic epithelial cell line SAF‐1, which may be important for persistence and establishment of a carrier state in S. aurata .

Temperature influences the expression of fimbriae and flagella in Hafnia alvei strains: an immunofluorescence study - D. Padilla; F. Acosta; J. A. García; F. Real; Jose R. Vivas (Archives of Microbiology, 2009)

Characterization of Monoolein-Based Lipoplexes Using Fluorescence Spectroscopy - J. P. Neves Silva; P. J. G. Coutinho; M. E. C. D. Real Oliveira (Journal of Fluorescence, 2008)

Genetic variation in the base excision repair pathway and bladder cancer risk - Jonine D. Figueroa; Núria Malats; Francisco X. Real; Debra Silverman; Manolis Kogevinas; Stephen Chanock; Robert Welch; Mustafa Dosemeci; Adonina Tardón; Consol Serra; Alfredo Carrato; Reina García-Closas; et al. (Human Genetics, 2007)

Growth and ion relations in response to combined salinity and waterlogging in the perennial forage legumes Lotus corniculatus and Lotus tenuis - N. L. Teakle; D. Real; T. D. Colmer (Plant and Soil, 2006)

Domain Formation in DODAB–Cholesterol Mixed Systems Monitored via Nile Red Anisotropy - Graham Hungerford; Elisabete M. S. Castanheira; Adelina L. F. Baptista; Paulo J. G. Coutinho; M. Elisabete C. D. Real Oliveira (Journal of Fluorescence, 2005)

Virulence factors and pathogenicity of Hafnia alvei for gilthead seabream, Sparus aurata L. - D Padilla; F Real; V Gómez; E Sierra; B Acosta; S Déniz; F Acosta (Journal of Fish Diseases, 2005)
Virulence factors ( eae gene, haemolytic capacity, fimbriae, resistance to the bactericidal effect of serum, siderophore production) and pathogenicity for gilthead seabream, Sparus aurata L., were analysed for 23 Hafnia alvei strains. None of the strains used in LD 50 studies were lethal for seabream at doses as high as >10 8 cfu mL −1 . In chronic challenge studies differences in severity of the inflammatory response were observed between strains. On the basis of correlation of the inflammatory response to different strains of H. alvei in seabream with those virulence factors studied, it was only possible to establish a positive correlation between pathogenicity and resistance to the bactericidal effect of fish serum. Gilthead seabream is thus a species with considerable resistance to experimental infection with H. alvei . The bacterium does, however, have the capacity to remain viable in seabream for up to 3 months, without any clinical signs. Hafnia alvei is a well‐recognized human and animal pathogen. Thus, as the pathogen can coexist with aquaculture operations, cultured gilthead seabream could represent a risk to human health as a carrier in some circumstances.

The interleukin-6 (−174) G/C promoter polymorphism is associated with type-2 diabetes mellitus in Native Americans and Caucasians - Barbora Vozarova; José-Manuel Fernández-Real; William C. Knowler; Lluis Gallart; Robert L. Hanson; Jonathan D. Gruber; Wilfredo Ricart; Joan Vendrell; Cristóbal Richart; P. Antonio Tataranni; Johanna K. Wolford (Human Genetics, 2003)

Monitoring the Phase Transition of C12E5/Water/Alkane Microemulsions Through Excimer Formation - M. E. C. D. Real Oliveira; Graham Hungerford; E. M. S. Castanheira; M. da G. Miguel; H. D. Burrows (Journal of Fluorescence, 2000)